Melt pool morphology in directed energy deposition additive manufacturing process. Issue 1 (May 2020) - Chen, Y; Clark, S; Leung, A C L; Sinclair, L; Marussi, S; Atwood, R; Connoley, T; Jones, M; Baxter, G; Lee, P D
Abstract: Directed Energy Deposition Additive Manufacturing (DED-AM) is one of the principal AM techniques being explored for both the repair of high value components in the aerospace industry as well as freeform fabrication of large metallic components. However, the lack of fundamental understanding of the underlying process-structure-property relationships hinders the utilisation of DED-AM for the production or repair of safety-critical components. This study uses in situ and operando synchrotron X-ray imaging to provide an improved fundamental understanding of laser-matter interactions and their influence on the melt pool geometry. Coupled with process modelling, these unique observations illustrate how process parameters can influence the DED-AM melt pool geometry. The calibrated simulation can be used for guidance in an industrial additive manufacturing process for microstructure and quality control.